IbM pelatihan supervisi manajerial bagi pengawas sekolah dasar di Kota Makassar - Muh. Ardiansyah; Ismail Tolla; Ratmawati Ratmawati (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The general objective of this activity is to improve the fulfillment of supervisor y managerial competencyimprovement needs which include aspects of management that are directly related to school efficiency and effectivenessincluding planning, coordination, implementation, assessment and development of educational human resource (HR)competencies and other resources . The target of community service activities is to make a real contribution to partners inmeeting the need to improve managerial supervision competencies for elementary school supervisors in Makassar City. Theamount of the managerial supervision quality conducted by supervisors to the principal of the primary school is largelydetermined by the quality of managerial supervision competencies. Therefore the solution adopted to improve supervisorsmanagerial competencies is to conduct